Workshop Transformasi Kelas Konvensional Ke Kelas Cerdas Guru Adaptif di Era Digital dan AI - Sella Mawarni; Maenuddin Bustanil Syah; Nuraini Yusuf; Nur Eva Yanti; Dedy Aswan (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
The era of Artificial Intelligence (AI) demands educators to transform from conventional teaching practices toward adaptive, technology-based smart classrooms. This community service activity aims to enhance the digital competence of teachers and lecturers in utilizing generative AI tools to design innovative and contextual learning media. The workshop was conducted online via Zoom, involving 24 educators from various educational institutions across Indonesia. The training covered three main platforms: Google Gemini for effective prompt engineering, NotebookLM for AI-based learning material management and synthesis, and the Magic Layer feature in Canva for interactive visual media development. The implementation method consisted of three stages: needs-based planning, an intensive 8-hour workshop, and evaluation and reflection using a satisfaction questionnaire. Evaluation results indicated very high participant satisfaction across all indicators, ranging from 89% to 96%, with acquisition of new knowledge scoring the highest (96%). Participants demonstrated significant improvement in technical, pedagogical, and collaborative dimensions, and exhibited a role shift from passive technology consumers to active creators of AI-based educational content. This activity proves that a practical, guided, and project-based workshop approach is effective in sustainably developing educators' digital competence in the era of digital transformation.